Class Metamorphosis - from traditional to Flipped to self-paced learning - Rozaimi, Abu Samah; Norazwina, Zainol; Nasratun, Masngut (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
Within the traditional learning environment, students might be left out unintentionally especially the struggling ones. The top students tend to get most of the attention in a lecture taught in a traditional model. Also, it is compulsory to cover specific contents in the courses and this requirement might hinder the implementation of active learning. With the access to the Internet, learning can be done outside of classroom. Our team changed the classroom setting to active and cooperative learning in our Numerical Methods and Optimization course. All instructional materials are made available in the UMP online platform known as KALAM as early as the first day of the new semester. Assessment schedule is also provided for the students to plan their learning activities. This approach drastically improves students’ attainment, not only in terms of grade but also their related soft-skills.